Biological Earth observation with animal sensors. (April 2022) - Jetz, Walter; Tertitski, Grigori; Kays, Roland; Mueller, Uschi; Wikelski, Martin; ,; Åkesson, Susanne; Anisimov, Yury; Antonov, Aleksey; Arnold, Walter; Bairlein, Franz; Baltà, Oriol; et al.
Abstract : Space-based tracking technology using low-cost miniature tags is now delivering data on fine-scale animal movement at near-global scale. Linked with remotely sensed environmental data, this offers a biological lens on habitat integrity and connectivity for conservation and human health; a global network of animal sentinels of environmental change.